Gambaran Kadar Ureum Serum pada Wanita Hamil Normal - Hajia, Muh. A.; Mongan, Arthur E.; Wowor, Mayer F. (eBiomedik, 2017)
Abstract: During pregnancy, there are a variety of anatomical, physiological, biochemical, and hormonal changes that greatly affect several organ systems. Functional changes resulted from hormonal changes, increased load due to fetal growth, and ureter obstruction due to uterus enlargement cause increased glomerular filtration rate (GFR) that indicates an increase in renal function. These changes are accompanied by altered plasma concentration of certain substances such as ureum. Increased GFR results in declining plasma urea level. This study was aimed to obtain the serum urea levels in women with normal pregnancy. This was a descriptive observational study. There were 30 blood samples obtained from normal pregnant women in public health centers at Minanga, Bahu, and Sario from October 2017 to November 2017. The results showed that 30 normal pregnant women (100%) had decreased serum urea, as follows: 12.33 mg/dl in the 1st trimester; 9.09 mg/dl in the 2nd trimester; and 11,8 mg/dl in the 3rd trimester. Conclusion: Serum urea of normal pregnant women in the 1st trimester was higher than in the 2nd and 3rd trimester.Keywords: normal pregnancy, ureaÂ Abstrak: Selama kehamilan, wanita mengalami perubahan anatomis, fisiologis, biokimia dan endokrin yang sangat memengaruhi beberapa sistem organ. Perubahan fungsi selama kehamilan karena efek hormonal, peningkatan beban dari janin, dan obstruksi ureter oleh rahim yang semakin membesar mengakibatkan peningkatan Glomerular Filtration Rate (GFR) yang merupakan indikasi peningkatan fungsi filtrasi ginjal disertai perubahan konsentrasi plasma. Sebagai hasil dari peningkatan GFR, ureum plasma menurun pada kehamilan. Penelitian ini bertujuan untuk mengetahui gambaran kadar ureum serum pada wanita hamil normal. Jenis penelitian ialah deskriptif observasional. Terdapat 30 sampel darah dari wanita hamil normal di Puskesmas Minanga, Bahu, dan Sario sejak Oktober-November 2017. Hasil penelitian mendapatkan 30 wanita hamil normal (100%) mengalami penurunan kadar serum ureum yaitu 12,33 mg/dl pada trimester I; 9,09 mg/dl pada trimester II; dan 11,8 mg/dl pada trimester III. Simpulan: Ureum serum pada wanita hamil normal trimester 1 lebih tinggi dibandingkan kadar serum ureum trimester 2 dan kadar serum ureum trimester 3.Kata kunci: hamil normal, ureum serum